Islet Autoantibody Patterns in Patients With Type 2 Diabetes Aged 60 and Higher: A Cross-Sectional Study in a Chinese Hospital - Li, Rumei; Huang, Jinya; Yu, Yifei; Yang, Yehong (Frontiers in Endocrinology, 2018)
Background Some elderly citizens with a clinical diagnosis of type 2 diabetes had evidence of positive islet autoantibodies. We aimed to discover their islet autoantibody patterns and independent correlative factors, which might lead to a better understanding of significance of islet autoimmunity in the progression of elderly diabetes. Methods A total of 541 inpatients of clinically diagnosed type 2 diabetes aged 60 and over were recruited. Three islet autoantibodies including IAA, ICA, GADA as well as clinical and biochemical characteristics were tested and collected in huashan hospital. Associations between these antibodies and clinical features were analyzed by spearman correlation and binary logistic analysis. Results In our current study, total positive rate of islet autoantibodies (IAA, ICA, GADA) was 35.67% with 26.62% for individual IAA, 5.55% for ICA and 5.91% for GADA respectively, in elderly type 2 diabetes. None of combinations of such autoantibodies were observed, with the exception of IAA + ICA (0.74%, n=4), IAA + GADA (1.48%, n=8) and ICA + GADA (0.18%, n=1) . Compared with GADA negative group, patients in positive group tended to have lower level of fasting and postprandial C peptide, fasting blood glucose and BMI. After adjustment for the BMI, fasting blood glucose, postprandial C peptide, fasting C peptide seemed to be an independent factor related with GADA positivity (OR=0.52, P=0.02).  As for patients with positive IAA, they were more likely to have insulin treatment with longer duration of diabetes, higher level of BMI and lower level of postprandial C peptide. After adjustment for the duration of diabetes, BMI and postprandial C peptide, insulin treatment was a significant predictor for IAA positivity (OR=5.20, P<0.0001). Furthermore, hs-CRP was positively related with ICA positivity, and hs-CRP appeared to be an independent indicator for ICA (OR=3.43, P=0.008). Conclusions In elderly type 2 diabetes, high prevalence rate of IAA was frequently accompanied by insulin treatment, while ICA and GADA were more closely associated with the systemic inflammation and beta cell failure respectively.